Multi-objective optimization and performance evaluation of rotary furnace refractory linings using locally sourced materials - Aragaw Mulu Muhaba (Advances in Mechanical Engineering)
This study optimizes refractory lining formulations for oil-fired rotary furnaces using locally sourced kaolin clay, processed into chamotte, and combined with raw kaolin, potter’s clay, and slaked lime. The Grey Taguchi method and grey relational analysis were employed to optimize cold crushing strength (CCS), thermal shock resistance (TSR), and open porosity (OP). Sixteen mixtures were prepared by varying material proportions, calcination temperature, and curing time. The optimal blend—70% chamotte, 28.5% raw kaolin, 6.5% pottery clay, and 1% slaked lime, calcined at 1350°C with 3 h of curing—demonstrated superior TSR and CCS while minimizing porosity. Confirmatory tests validated the formulation’s reliability, with results within a 95% confidence interval. ANOVA identified TSR as the most significant performance factor. The study highlights the effectiveness of combining Taguchi methods with grey relational analysis for multi-objective optimization, balancing competing performance metrics in refractory development. Industrial testing showed the optimized bricks withstanding over 30 furnace cycles, achieving a maximum service temperature of 750°C, and exhibiting improved energy efficiency (60%). These results demonstrate the potential of locally sourced materials to reduce reliance on imports and address challenges in the Ethiopian refractory industry. The findings contribute to sustainable, cost-effective refractory solutions for high-temperature industrial applications, promoting local production and resource utilization.